“ANÁLISIS FINANCIERO Y ESTUDIO DE CAPITAL DE TRABAJO DE LA EMPRESA DE SERVICIO DE LIMPIEZA ULTRACLEANING G&R CÍA.LTDA., DE LA CIUDAD DE LOJA, PERÍODOS 2015-2016 - Gañay Urgilez, Yesenia Marisol (2018)
The thesis work titled, "FINANCIAL ANALYSIS AND WORK CAPITAL STUDY OF THE SERVICE COMPANY OF CLEANING ULTRACLEANING G&R CÍA.LTDA., OF THE CITY OF LOJA, PERIODS 2015-2016", was carried out based on the objectives set to determine the real and financial economic situation of the company according to the years subject to study. For its development the general objective was to carry out the financial analysis and study of working capital of the cleaning service company ULTRACLEANING G & R Cía.Ltda, of the city of Loja to know its economic-financial situation for the periods 2015-2016 , for which the following specific objectives were determined: the first objective is to prepare a vertical and horizontal analysis to the company to determine the increases or decreases and all those positive and negative changes that the financial statements have suffered from one period to another, which was fulfilled by obtaining reliable information from part of the owner of the company, being necessary to carry out the restructuring of the financial statements in order to develop the vertical and horizontal analysis that allowed knowing the variations that the financial statements had from one period to another; the second objective is to apply the economic value added (EVA) to calculate the capacity of the cleaning services company ULTRACLEANING G&R Cía. Ltda, to generate wealth taking into account the efficiency and productivity of its assets, which was developed by means of the application of the 6 formula of the economic value added indicator (EVA), which facilitated knowing the economic benefit that the company had to generate economic profitability according to its assets; the third objective is to conduct a study of working capital in order to determine that each of the circulating accounts of the company maintain an acceptable level, for this financial indicators were applied with respect to accounts receivable, inventory and accounts to pay that allow to determine the resources that the company has to generate profitability; the fourth objective is to present a report of the results of the financial analysis and the study of working capital to the cleaning services company ULTRACLEANING G&R Cía.Ltda, detailing the possible situations that help to make future decisions, same that was fulfilled through the completion of the financial report composed of the letter of presentation, analysis and interpretation of the results with their respective conclusions and recommendations that they will allow the owner of the company to take timely decisions to improve their liquidity and profitability. For the development of the thesis work and the obtaining of the results, the financial information related to the ULTRACLEANING company was compiled in a general way, and through logical procedures, the relevant information was identified and simplified in the review of the literature in accordance to the topic of thesis, for the respective restructuring of the financial statements and the application of the financial analysis, facilitating knowing the most representative accounts that the company has; the results of the financial analysis and study of working capital of the company were 7 then interpreted, which allowed concluding with the financial report, inserting their respective conclusions and recommendations. Finally, it was concluded that the company ULTRACLEANING has a decrease of current assets in 2016 for a value of $44.657,94 because the account and accounts receivable account decreased due to the fact that the company is not applying adequate policies i charge your clients; in reference to income from ordinary activities, the company in 2016 had an increase in sales of $137.555,73 that is, there was a high level of provision of cleaning services to the public sector; when applying the economic value added indicator (EVA) it was evident that in 2016 there was an increase of $24,209.50 which means that the company has obtained a favorable economic benefit that allows it to improve its economic and financial situation; the company has a profitable working capital of $8,211.25, which allows it to continue operating with its economic activities.